Reducing emissions from deforestation and forest degradation (Redd+) in the municipality of Cachoeiras de Macacu, RJ-Brazil: feasibility determination through an environmental governance analysis. - FLORES AGUILAR, A. (2012)
Reducing Emissions from Deforestation and Forest Degradation (REDD+) developed under the United Nations Framework Convention on Climate Change (UNFCCC), constitutes one mechanism that could help address both the reduction of the share of the Greenhouse gas (GHG) emissions and the forest management issues that occur in the Brazilian Mata Atlântica. The current research analyses the feasibility of the incorporation of REDD+ in the municipality of Cachoeiras de Macacu, Rio de Janeiro Brazil. In order to do so, a strategic analysis of the elements of the REDD+ Framework (i.e. baseline, scope, funding instruments and, distribution mechanisms) and the elements of the Brazilian multi-scalar environmental frameworks was done. The hereditary landownership system, intensive industrial and urban growth, lack of knowledge of REDD+ by authorities, and inconsistencies in the law, represent some of the major obstacles to incorporate the mechanism into the study area. Nevertheless, the existence of public and private initiatives such as the “Reservas Particulares do Patrimônio Natural” (RPPN), the “Plano de Areas Verdes,” and the creation of “Monumentos Naturales,” open a window of opportunity for the incorporation of REDD+. Civil society´s participation is also an important factor present in the area of study. Actors like the “Reserva Ecológica de Guapiaçu“ (REGUA), “Ecologia Interior“ (ECOIN), consist of valuable allies for potential REDD+ developments. Other instruments like the ICMS-ecológico, “Mercado Brasileiro de Reduções de Emissões” (MBRE), and several multi-scalar funding instruments, should be analyzed in order to determine their compatibility with REDD+.